Employee Performance Assessment System Design Based on Competence - Senen, Syamsul H.; Sumiyati, Sumiyati; Masharyono, Masharyono (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2017)
Employees are one of the most important components owned by the organization in achieving the purpose. Success or failure an organization in exercised their activities related to the capacity of employees (competence) works in the organization. Therefore need to may system does performance evaluation of can give picture of the performance of employees. This research method is divided into five phases as preparation phase, the data collection phase, phase data processing, phase analysis, stage design system, system testing is limited. The results of this study to design employee performance evaluation system based on competency by name spkp-sms.org